Oil & Gas production in Venezuela: Analysis by Cobb-Douglas function (2019)
The production of energy is directly related to the growing demand and excessive dependence on the production of fossil resources, that is, coal, oil and natural gas, which must be planned in a safe, clean, efficient and sustainable scenario. The objective of this paper is to analyze oil production in the Bolivarian Republic of Venezuela during the period between 2002 and 2015. An econometric model was developed using the Cobb-Douglas production function, and the results obtained allowed observing the existing gap between real production and the goals proposed by the Venezuelan state.